2013
DOI: 10.2478/s11535-013-0212-y
|View full text |Cite
|
Sign up to set email alerts
|

Edible flowers — antioxidant activity and impact on cell viability

Abstract: The phenolic compound composition, antioxidant activity and impact on cell viability of edible flower extracts of Allium schoenoprasum; Bellis perennis; Cichorium intybus; Rumex acetosa; Salvia pratensis; Sambucus nigra; Taraxacum officinale; Tragopogon pratensis; Trifolium repens and Viola arvensis was examined for the first time. Total phenolic content of the flowers of these plants fell between 11.72 and 42.74 mg of tannin equivalents/kg of dry matter. Antioxidant activity ranged from 35.56 to 71.62 g of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
3
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 55 publications
5
23
3
2
Order By: Relevance
“…Organosulphur compounds, including 2,4-dimethylthiophene, 3,4-dimethylthiophene, methyl propyl disulphide and dimethyl trisulphide, have been detected qualitatively in the flowers (Grzeszczuk et al, 2011;Sobolewska et al, 2015). In addition, phenolic compounds have been isolated including gallic acid, coumaric acid, ferulic acid, rutin and other flavonoids, and polyphenolic compounds (Fossen et al, 2000;Kucekova et al, 2013;Lopez-Garcia et al, 2013).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Organosulphur compounds, including 2,4-dimethylthiophene, 3,4-dimethylthiophene, methyl propyl disulphide and dimethyl trisulphide, have been detected qualitatively in the flowers (Grzeszczuk et al, 2011;Sobolewska et al, 2015). In addition, phenolic compounds have been isolated including gallic acid, coumaric acid, ferulic acid, rutin and other flavonoids, and polyphenolic compounds (Fossen et al, 2000;Kucekova et al, 2013;Lopez-Garcia et al, 2013).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Considering the mass public health management especially in the poor and developing countries, it is necessary to conduct the routine assay of the antibacterial activity of the frequently used herbal medicines besides the notification of their microbiological quality. Several reports have been published so far regarding the presence of antibacterial activity of the natural plants and plant extracts [8][9]11 However, In Bangladesh, a number of studies have been initiated the existence of such antibacterial activity of the commonly available herbal medicines used by the people 1,12 . As the continuation of our recent findings, present study revealed such trend in 6 more commonly available herbal medicines.…”
Section: In Vitro Antibacterial Activity Of the Herbal Medicine Samplesmentioning
confidence: 99%
“…An important aspect of using huge amount of antibiotics comes up with the emergence of drugresistant bacteria in food, water and pharmaceutical products which in turn may bring serious obstacle in disease medication as well as may reduce the rate of self immune response 1,[6][7] . Conversely, several studies have revealed that the herbs and herb extracts can effectively reduce the pathogenic propagation with the minor side effects and small toxicity [8][9][10][11] . Moreover, compared with the synthetic antibiotics, herbal medicines may also be effective in managing the dissemination of drug-resistant pathogenic microorganisms [1][2]8 .…”
Section: Introductionmentioning
confidence: 99%
“…Plants have the ability to synthesize a wide range of chemical components with numerous beneficial effects to treat human disease complications (1,2). Apart from antibiotic therapy which is currently known to face the shortfall of drug-resistant microorganisms, use of herbal medicines gained its acceptance in recent days (3)(4)(5)(6)(7)(8)(9)(10)(11). Several studies have been reported to possess the antioxidant activity of plants with wound-healing effects as well as to prevent the formation and oppose the action of toxic radicals (8,(12)(13)(14).…”
Section: Estimation Of Microbiological Propagation and Antimicrobial mentioning
confidence: 99%